2023
DOI: 10.1136/jitc-2023-006814
|View full text |Cite|
|
Sign up to set email alerts
|

Selective immune suppression using interleukin-6 receptor inhibitors for management of immune-related adverse events

Abstract: BackgroundManagement of immune-related adverse events (irAEs) is important as they cause treatment interruption or discontinuation, more often seen with combination immune checkpoint inhibitor (ICI) therapy. Here, we retrospectively evaluated the safety and effectiveness of anti-interleukin-6 receptor (anti-IL-6R) as therapy for irAEs.MethodsWe performed a retrospective multicenter study evaluating patients diagnosed with de novo irAEs or flare of pre-existing autoimmune disease following ICI and were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…Because our results suggested that the IL-6 classical signaling, but not trans-signaling, may be related to the anti-tumor immune responses in NSCLC patients treated with ICIs, anti-IL-6 or anti-IL-6R Abs, but not sgp130 fusion proteins, may be promising to improve the efficacy of ICIs. Indeed, combined ICI and anti-IL-6 or anti-IL-6R Abs have been reported to potentially enhance anti-tumor immunity or reduce immune-related toxicity in preclinical ( Mace et al, 2018 ; Hailemichael et al, 2022 ) and clinical studies ( Fa’ak et al, 2023 ). Therefore, to facilitate personalized immunotherapy, further clinical trials are recommended to validate the effects of anti-IL-6 or anti-IL-6R Abs in ICI-treated NSCLC patients with high plasma IL-6 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Because our results suggested that the IL-6 classical signaling, but not trans-signaling, may be related to the anti-tumor immune responses in NSCLC patients treated with ICIs, anti-IL-6 or anti-IL-6R Abs, but not sgp130 fusion proteins, may be promising to improve the efficacy of ICIs. Indeed, combined ICI and anti-IL-6 or anti-IL-6R Abs have been reported to potentially enhance anti-tumor immunity or reduce immune-related toxicity in preclinical ( Mace et al, 2018 ; Hailemichael et al, 2022 ) and clinical studies ( Fa’ak et al, 2023 ). Therefore, to facilitate personalized immunotherapy, further clinical trials are recommended to validate the effects of anti-IL-6 or anti-IL-6R Abs in ICI-treated NSCLC patients with high plasma IL-6 levels.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to corticosteroids that generally suppress various inflammatory pathways, cytokine inhibitors offer a more precise clinical method to diminish inflammation caused by ICIs in NSCLC 91 . Cytokine inhibitors, including anti‐TNF‐α agents (infliximab, etanercept, adalimumab) and anti‐IL‐17A agents (secukinumab) inhibitors, as well as cytokine receptor inhibitors, such as IL‐6 (tocilizumab) or IL‐α4β7 receptor (vedolizumab) inhibitors, have been investigated for their efficacy in managing steroid‐resistant irAEs in NSCLC 91,158,178 . Notably, TNFα inhibition has shown effectiveness in treating severe and refractory irAEs, such as colitis, inflammatory arthritis and hepatitis, in NSCLC and other cancer types 179‐181 .…”
Section: Management Strategies To Abrogate Iraes Of Icis In Nsclcmentioning
confidence: 99%
“…Notably, TNFα inhibition has shown effectiveness in treating severe and refractory irAEs, such as colitis, inflammatory arthritis and hepatitis, in NSCLC and other cancer types 179‐181 . A recent multicentre study found that inhibition of the IL‐6 receptor improved irAEs in 73% of patients with NSCLC and other cancers without affecting tumour immunity 178 . Additionally, tocilizumab was notably effective in treating nivolumab‐induced pneumonitis, with a 79.4% positive response in patients with NSCLC 158 .…”
Section: Management Strategies To Abrogate Iraes Of Icis In Nsclcmentioning
confidence: 99%
“…In the recent meta‐analysis, TNF‐α blockade is the most reputable strategy in the management of steroid‐refractory ICIs‐induced enterocolitis 112 . Recently, a retrospective multicenter study assessed the impact of anti‐IL‐6R therapy on irAEs and antitumor immune response 113 . The administration of anti‐IL‐6R antibodies (tocilizumab or sarilumab) resulted in a rapid improvement in irAEs including inflammatory arthritis, hepatitis/cholangitis, encephalitis, polymyalgia rheumatica, diffuse systemic sclerosis, interstitial nephritis.…”
Section: Treatment Of Immune‐related Adverse Events By Targeting Trm ...mentioning
confidence: 99%